WORKPLACE STRECHING EXERCISE AND GIVING SWEET TEA IMPROVE PHYSIOLOGICAL RESPONSE AND INCREASE THE PRODUCTIVITYAMONG TAILORS IN PT. FUSSION HAWAI - Ni Wayan Rusni; Ketut Tirtayasa; I Made Muliarta (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2017)
Employment in the garment industries involves a lot of human resources as workers, especially those in the sewing sector. Workers who work in the garment industry have higher possibility to suffer musculoskeletal disorders compared with those in other industries. Less ergonomic working postures is one of the factors that can affect the quality and quantity of the tailor’s work. Lack of rest time and nutrition of the workers are also additional factor for the musculoskeletal complaints and fatigue in workers that will ultimately impact to the productivity. Therefore, ergonomic intervention is needed in forms of workplace stretching exercise and giving sweet tea to overcome the condition. This research was an experimental study using treatment by subject design on 25 samples selected by simple random sampling method. Interventions given were WSE and sweet tea. Data were collected three times before and after intervention with washing out period for one day. The data collected comprised subjective fatigue using questionnaire of 30 items of fatigue, data for the musculoskeletal complaints used questionnaire of nordic body map, and also employ productivity by calculation partial productivity. Data analysis was done initially by the descriptive analysis with the significance’s level ?=0.05 and the normality data tested with Shapiro-Wilk. Subsequently, the data with normal distribution were analyzed by t-paired, while the data with abnormal distribution analyzed be Wilcoxon test. The results showed, there was decrease of musculoskeletal complaints of 24.98%, decrease of fatigue 27.06%, and increase of labor productivity 66.67% all were significant (p<0.05). Inconclusion, the ergonomic intervention with WSE and giving sweet tea can improve the physiologic response as shown decrease of fatigue and musculoskeletal complaints as well as increase of labor productivity of the tailors. It is recommended that the study results be applied by tailors working in garment industry or individually.